Case Report: Long segmental lesions of the spinal cord caused by exposure to xylene - Du, Qin; Chen, Hongxi; Shi, Ziyan; Zhou, Hongyu (Frontiers in Neurology, 2023)
Xylene has the potential to cause nervous system disturbances since it is a lipophilic substance with high affinity for lipid-rich tissue, such as the brain. Involvement in the spinal cord, especially long segmental spinal cord lesions that permeate almost the entire cervical and thoracic spinal cord, is extremely rare. We report two cases of occupational exposure to excessive xylene, both of which presented with severe and rapidly progressive numbness and weakness in the limbs that, more importantly, led to poor outcomes: one died and the other was left severely disabled. In both, spinal magnetic resonance imaging showed long segmental lesions in the cervicothoracic spinal cord. These findings may provide some insights into the effects of xylene as an isolated agent on the spinal cord injury.